2020
DOI: 10.18178/ijiet.2020.10.10.1451
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Factors Based on an Extended UTAUT Model to Confirm Computer Science Instructors’ Behavioural Intention to Adopt the Flipped Classroom

Abstract: In terms of technology used to improve education, the flipped classroom provides an opportunity to enhance the teaching experience for both learners and educators. Studies have shown that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Hence, educators found it challenging to employ the flipped classroom in certain subjects and preferred the traditional teaching method instead (Cevikbas & Kaiser, 2020). Even though some educators think conventional teaching methods are preferable for a specific topic, Bakheet and Gravell (2020) discovered that they still preferred and intended to use flipped classroom approaches to create a better teaching method. For example, through the flipped classroom approach, educators or teachers can play their roles in assisting students' work and help them find their own solutions rather than mandating one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, educators found it challenging to employ the flipped classroom in certain subjects and preferred the traditional teaching method instead (Cevikbas & Kaiser, 2020). Even though some educators think conventional teaching methods are preferable for a specific topic, Bakheet and Gravell (2020) discovered that they still preferred and intended to use flipped classroom approaches to create a better teaching method. For example, through the flipped classroom approach, educators or teachers can play their roles in assisting students' work and help them find their own solutions rather than mandating one.…”
Section: Discussionmentioning
confidence: 99%
“…As this study intended to determine the motivation and intention of educators in adopting a flipped classroom, the UTAUT model was utilized to explore the individual acceptance of this new technology (Ventakesh et al, 2003). It is evident in the previous literature that technology acceptance models, specifically the UTAUT model, have been employed in studies related to e-learning and flipped classrooms (e.g., Abd Rahman et al, 2021;Bakheet & Gravell, 2020;Gunasinghe & Nanayakkara, 2021;Long et al, 2018;Radovan & Kristl, 2017). Hence, this model best underpins the motivation and intention to use the new pedagogy concerning technology usage.…”
Section: Measuring Motivation and Intention Of Teachers In Using Flippedmentioning
confidence: 99%
“…Although previous SCT studies described anxiety and self-efficacy as significant determinants of use intention (Compeau et al, 1999;Higgins, 1995), Venkatesh et al's (2003) original study did not include these two constructs as direct determinants of behavioral intention. Nonetheless, previous studies on e-learning using the UTAUT model have found that both anxiety and self-efficacy play a substantial role in e-learning acceptance (Sattari et al, 2017;Bakheet and Gravell, 2020).…”
Section: Acceptance Of Workplace E-learningmentioning
confidence: 96%
“…In a workplace where e-learning use is supported, employees are more likely to adopt it. Although the influence of facilitating conditions on e-learning usage has been supported in various studies, the context of most of these studies was higher education (Sattari et al , Abdekhoda and Gavgani, 2017; Bakheet and Gravell, 2020). Only a few studies have examined the relationship between facilitating conditions and e-learning usage in the context of corporate learning (Yoo and Han, 2013; Yoo et al , 2015; Yoo and Huang, 2016; Lin et al , Huang and Zhang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Those factors were discussed deeply in previous related work [22], in addition to previous work [23], which introduced the interviews process, methods to analyze the qualitative collected data, and findings of the qualitative data regarding the five proposed factors.…”
Section: Findings Of the Qualitative Studymentioning
confidence: 99%